Напишите сумму двух выражений и упростите его :
а) -4-m и m+60,1
б)1,1+a и -26-a
в)a+13 и -13+b
г)a+b и p-b
д)-m+n и -k-n
е)m-n и n-m

2

Ответы и объяснения

2013-03-29T22:23:44+04:00

а)(-4-m)+(m+60.1)=-4-m+m+60.1=56,1

б)(1,1+а)+(-26-а)=1,1+а-26-а=-24,9

в)(а+13)+(-13+b)=а+13-13-b=а-b

г)(a+b)+(p-b)=a+b+p-b=a+p

д)(-m+n)+(-k-n)=-m+n-k-n=-m-k

е)(m-n)+(n-m)=m-n+n-m=0

2013-03-29T22:42:25+04:00
А) (-4-m)+(m+60,1)=-4-m+m+60,1=56,1
б) (1,1+а)+(-26-а)=1,1+а-26-а=-24,9
в) (а+13)+(-13+b)=a+13-13-b=a-b
г) (a+b)+(p-b=a+b+p-b=a+p